KELAYAKAN SAKSI DALAM PEMBUATAN AKTA JUAL BELI HAK MILIK ATAS TANAH OLEH PEJABAT PEMBUAT AKTA TANAH - Marlianus Siki, Renhat; Agung, I Gusti Nyoman; Darmadha, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014, 2014)
Property right over land can be transferred through the sale and purchase. By buyingand selling, title for the land to move from the land owner as the seller to another partyas a buyer. Land purchase agreement is set forth in the deed of sale of land issued bythe Land Deed Official (PPAT) is a proof of the above legal actions that lead to the civilright of a person or corporation on the ground. In the making of deed of sale of landrequired witnesses who knew about the contents of the deed. Purpose research is toknow what the terms to be a witness in making of deed of sale of land title before LandDeed Official (PPAT) and Land Deed Official (PPAT) how the role of witness todetermine feasibility in making the deed of sale land rights which have not beenregistered and has been registered. This type of research is used in this paper is a typeof normative study that describes the requirements to become a witness in the making ofdeed of sale of land titles before the Land Deed Official (PPAT). Requirements tobecome a witness in the manufacture of a dedd of sale of land titles contained in Law of40 number (1) on job title notary. Land Deed Official (PPAT) role in determining thefeasibility of a witness in the making of deed of sale of land titles which have not beenregistered, Land Deed Official (PPAT) can use at least two witnesses, namely the headof the village and a member of village government or village lies the respective plots ofthe local environment.Where as in determining the feasibility of a witness in a deedselling land titles were certified, the witness used by Land Deed Official (PPAT) is LandDeed Official (PPAT) employees who meet the requirement to become a witness in theinauguration of deed.
Keywords: Land Property Right, Deed of Sale, Functionary of Maker of Act of Land (PPAT), Witness